Remembering the Wars Commemoration in Western Australian Communities - Stephens, John; Seal, G. (Black Swan Press, 2015)
This book – Remembering the Wars: Commemoration in Western Australian Communities – explores these questions and shows how the story of war remembrance in Western Australia can be revealed through the memorial places that communities build to commemorate their local heroes. Through a representative selection of Western Australian war memorials, this book illustrates that while Anzac continues to be a prime motivation for war remembrance there are significant local interpretations and representations of the national story. It is the collection of these local and individual negotiations that give Western Australian war commemoration its unique perspective and flavour. Further they reflect changing community attitudes and values in relation to military conflicts and their consequences, including the ambitions and sorrows of its people.